2015
DOI: 10.1634/theoncologist.2014-0247
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Assessment-Identified Deficits in Older Cancer Patients With Normal Performance Status

Abstract: Background. We investigated whether a brief geriatric assessment (GA) would identify important patient deficits that could affect treatment tolerance and care outcomes within a sample of older cancer patients rated as functionally normal (80%-100%) on the Karnofsky performance status (KPS) scale. Methods. Cancer patients aged $65 years were assessed using a brief GA that included both professionally and patientscored KPS and measures of comorbidity, polypharmacy, cognition, function, nutrition, and psychosocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
116
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 200 publications
(124 citation statements)
references
References 51 publications
4
116
0
4
Order By: Relevance
“…KPS), may reveal problems relevant to cancer care that are both amendable, and may otherwise go unrecognized (9, 49). In this sample, a majority (65%) of older adults with had a least one functional deficit defined with specific sections of the GA and chosen as being amenable by OT/PT.…”
Section: Discussionmentioning
confidence: 99%
“…KPS), may reveal problems relevant to cancer care that are both amendable, and may otherwise go unrecognized (9, 49). In this sample, a majority (65%) of older adults with had a least one functional deficit defined with specific sections of the GA and chosen as being amenable by OT/PT.…”
Section: Discussionmentioning
confidence: 99%
“…A brief geriatric assessment (GA) [18, 19] that our research team has used in several geriatric oncology studies [5, 2023] will be used to determine if the patient has a functional deficit. The specific scales within the GA used for this functional deficit screen are described in detail below.…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, very few data are available in older patients. A study on trends in 21-gene recurrence score (RS) assay use among 132,222 women aged [66][67][68][69][70][71][72][73][74] and 75-94 years with BC post-surgery revealed no change in chemotherapy use despite increased RS testing and associated cost in patients ≥75 years [44]. Recent SEER database study (30% of patients aged ≥70years) reported a high BC-specific mortality for older patients with either no 21-gene assay performed or a RS ≥18, but not <18 [45].…”
Section: Role Of Adjuvant Systemic Therapy In Early Breast Cancementioning
confidence: 99%
“…Performance status does not appear to be sufficient for differentiating the heterogeneous older population with cancer [69,70]. Geriatric syndromes, i.e.…”
Section: Role Of Geriatric Assessments In Breast Cancer Treatmentmentioning
confidence: 99%